2021
DOI: 10.1016/j.apsb.2021.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological insights into autophagy modulation in autoimmune diseases

Abstract: As a cellular bulk degradation and survival mechanism, autophagy is implicated in diverse biological processes. Genome-wide association studies have revealed the link between autophagy gene polymorphisms and susceptibility of autoimmune diseases including systemic lupus erythematosus (SLE) and inflammatory bowel disease (IBD), indicating that autophagy dysregulation may be involved in the development of autoimmune diseases. A series of autophagy modulators have displayed protective effects on autoimmune diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 178 publications
(221 reference statements)
0
11
0
Order By: Relevance
“…Various previous studies have reported that autophagy is constitutively active in chondrocytes (26,27). Appropriate autophagy has a housekeeping role in preventing diseases such as cancer, cardiomyopathy, diabetes, liver diseases and autoimmune diseases, as well as neurodegeneration and infections (28)(29)(30)(31)(32)(33)(34). It is a well-conserved mechanism and has been confirmed to be important in various physical events.…”
Section: Discussionmentioning
confidence: 99%
“…Various previous studies have reported that autophagy is constitutively active in chondrocytes (26,27). Appropriate autophagy has a housekeeping role in preventing diseases such as cancer, cardiomyopathy, diabetes, liver diseases and autoimmune diseases, as well as neurodegeneration and infections (28)(29)(30)(31)(32)(33)(34). It is a well-conserved mechanism and has been confirmed to be important in various physical events.…”
Section: Discussionmentioning
confidence: 99%
“…The comprehensive and systematic analysis of drugs-active-ingredients-target proteins in network pharmacology conforms to the holistic concept, and its research concept coincides with the overall concept of TCM syndrome differentiation and treatment. Network pharmacology is often used in the study of TCM components and targets [ 32 37 ], especially TCM compound prescriptions. Different chemical components in TCM compounds may have synergistic effects in terms of reducing toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…ULK1 also activates autophagy by phosphorylation of downstream proteins to participate in the regulation of some stress mechanisms. Excepted for lapidating LC3B and driving the formation of autophagosomes, ATG16L1 is also a direct ULK1 target and regulated by ULK1 phosphorylation at Ser278 during stress 153 . In addition, based on proteomic methods combined with experimental methods, it was found that ULK1 phosphorylated SEC16A at Ser846, promoting the assembling COPII components in ERES, and regulating the transport of ER to the Golgi apparatus 154 .…”
Section: The Molecular Basis Underlying the Regulation Mechanism Of Ulk1mentioning
confidence: 99%
“…In lung inflammation and even acute lung injury under influenza A virus infection, lacking of HIF-1 α decreases glycolysis levels and promotes autophagy through the AMPK α /ULK1 pathway to promote IAV copy 252 . Moreover, under infectious conditions, ULK1 kinase, can directly phosphorylate ATG16L1, and phosphorylated ATG16L1 localizes to the site of internalizing bacteria and promotes antimicrobial autophagy, a process implicated in Crohn's disease, and the mechanism remains to be investigated 153 .…”
Section: Autophagic and Non-autophagic Functions Of Ulk1 In Human Dis...mentioning
confidence: 99%